Compressive and cyclic loading of silicone breast implants and their effect on shape resilience and reliability of the shell material - Schubert, Dirk W.; von Hanstein, Harald; Daenicke, Jonas; Werner, Siegfried; Horch, Raymund E. (Polymer International, 2018)
The mechanical behavior of gel-filled silicone breast implants has been examined as well as the mechanical properties of the implant shell itself. For the first time the implants were tested under compression in two different ways. Subsequently the implant shell material was analyzed by tensile test on dumbbell-shaped specimens. The results are presented in contour plots which provide a detailed view of the measured values of the samples. Finally a statistical failure analysis was carried out by means of a Weibull fit to provide further data on the mechanical behavio
Keywords: Compression test; cyclic loading; mechanical properties; silicone breast implant; tensile test